Efektivitas Pengetahuan Keluarga dalam Pemberian Jus Buah Alpukat pada Pasien Hiperkolesterolemia - Reski Mardana; Nurhayati Nurhayati (Sarana Ilmu Indonesia (salnesia), 2021)
Consuming avocado can maintain heart health. Avocados are rich in compounds called beta-sitosterol which have been shown to be effective in lowering blood cholesterol levels. This literature review aimed to analyze the effectiveness of family knowledge in administering avocado juice to hypercholesterolemic patients. The quantitative this study explores evidence published in electronic databases such as Google Scholar and Pubmed, using a search strategy, we identified 4 articles that are objectives potentially and relevant to the research objectives and these articles were included in the final analysis. This study showed the effectiveness of family knowledge in administering avocado juice to hypercholesterolemic patients. in results of research from several articles in in literature review indicate to family knowledge is effective in administering avocado juice to hypercholesterolemic patients.